sgRNA design and in vitro nucleolytic analysis of the Cas9‐RNP complex for transgene‐free genome editing of the eIF4E1 gene from Capsicum an‐ nuum L. - Josefanny Tham; Alfred Patisenah; Tommy Octavianus Soetrisno Tjia; Santiago Signorelli; Intan Taufik; Karlia Meitha (Universitas Gadjah Mada, 2023)
Chili (Capsicum annuum L.) is a highly valued vegetable, renowned for its unique taste and aroma. However, chili production faces challenges in meeting the high demand due to infections caused by pathogens such as ChiVMV (potyvirus). Previous studies have suggested that chili eIF4E1 plays a crucial role in potyvirus gene transcription. Therefore, this study explores the potential of CRISPR‐Cas9‐based genome editing to enhance chili resistance by introducing premature stop codons or truncated proteins. Two sgRNAs were designed, targeting the first and second intron of the eIF4E1 gene. The production of Cas9 protein was assessed with varying IPTG concentrations in Escherichia coli BL21(DE3), carrying 4xNLS‐pMJ915v2‐sfGFP plasmid with a TEV protease cut‐site at the N terminal. The findings indicate that the optimal IPTG concentration is 500 µM. Purification using an IMAC column confirmed the presence of Cas9 in the initial 2 mL of the eluted fractions, as indicated by numerous background proteins. Nevertheless, successful formation of Cas9‐RNP complexes was achieved for both sgRNAs. The nucleolytic activity of Tag‐Cas9 (carrying the MBP‐tag) and Cas9 was confirmed through in vitro endonuclease activity assays. The next step involved transfecting chili protoplasts with these RNP complexes to edit the chili eIF4E1 gene.